Popular Sovereignty, Islam, and Democracy - Glenn E. Perry (International Institute of Islamic Thought, 2003)
This article examines the idea that Islam’s rejection of popular sovereignty makes it incompatible with democracy. I show instead that sovereignty (“absolute despotic power,” popular or otherwise) is a sterile, pedantic, abstruse, formalistic, and legalistic concept, and that democracy should be seen as involving “popular control” rather than “popular sovereignty.” Divine sovereignty would be inconsistent with democracy only if that meant – unlike in Islam – rule by persons claiming to be God or His infallible representatives. A body of divine law that humans cannot change would be incompatible with democracy only if it were so comprehensive as to leave no room for political decisions.